Front Cover: Memristive Devices for Quantum Metrology (Adv. Quantum Technol. 5/2020). Issue 5 (8th May 2020) - Milano, Gianluca; Ferrarese Lupi, Federico; Fretto, Matteo; Ricciardi, Carlo; De Leo, Natascia; Boarino, Luca
Abstract : In the light of the revision of the International System of Units (SI), in article number 2000009 Gianluca Milano and co‐workers discuss on the possibility of using memristive devices for quantum metrology. Exhibiting quantized conductance phenomena in air at room temperature, memristive devices can be exploited for the realization of a resistance standard implementable on‐chip for self‐calibrating systems with zero‐chain traceability.